Planning ahead for implementation of long-acting HIV prevention: challenges and opportunities. Issue 4 (July 2015) - Meyers, Kathrine; Golub, Sarit A.
Abstract : Purpose of review: Broad-based access, uptake, and dissemination of daily oral HIV preexposure prophylaxis (PrEP) have been slow, despite strong evidence for efficacy. Effective and efficient implementation of long-acting HIV prevention products will require both analysis of the dynamics and determinants of daily oral PrEP implementation and identification of the distinct challenges and opportunities inherent in emerging technologies. Recent findings: Evidence suggests the importance of addressing implementation issues at three levels: patient, provider, and system. Patient-level factors include targeted education and messaging, tailored supports to enhance acceptability and uptake, and effective strategies for promoting adherence/persistence and retention in care. Provider-level factors include engaging a broad mix of providers, while ensuring adequate training and support for patient assessment, counseling, and follow-up. Systems-level factors include optimal delivery modalities, resource allocation, and ensuring access to populations most in need of new prevention options. Summary: Formative social/behavioral research must be undertaken proactively to prepare for and address future implementation challenges and reduce the gap between proving efficacy in clinical trials and assuring real-world effectiveness. Conceptualizing new HIV prevention technologies as behavioral interventions at the level of the patient, provider, and system will be paramount to effective and efficient implementation.